Evaluation of Community Participation and Fire and Rescue Sub-dept. In Fire Prevention Tanjung Priuk District - Ardani Ardani; Djaka Permana (Yayasan Ilomata, 2019)
This study aims to determine the level of community participation in fire prevention and management in Tanjung Priuk Subdistrict, the City of Administration against Fire Disasters in North Jakarta, the theory used in this research is the opinion of M. Nuh Minister of Education in the era of President Bambang Yudhoyono in Climbing the Amstein ladder to organize an ideal participation. The research method used is a qualitative method to obtain key data from interviews with legitimate sources that are directly involved in fire prevention and management and are supported by data from field observations. The data is then analyzed by the triangulation process. To find out the level of community participation. The results showed that the level of participation in fire prevention in Tanjung Priuk District had a range of information, consultations and appointments. the training program, which is carried out as an annual program, is provided for the community to provide information one way. In the management process, the community is at the second level of the seventh stage because the community is already a partner in the fire department before the fire department arrives at the fire location, the community has tried to extinguish the fire independently. To increase community participation in fire prevention and management, the Fire Department of the North Jakarta City Administration Office must optimize human resources, as well as other fire management resources, to be able to act also to provide costs for Balakar (Voluntary Fire) every month.